Effects of Rehabilitation Program to the Children in Conflict with the Law: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The rehabilitation program for children-in-conflict-with-the-law (CICL) in  Bahay Kalinga, Tahanan Mapagpala Center, is one of the many programs in Quezon City, in coordination with PNP and DSWD and per Republic Act 9344, or the Juvenile Justice and Welfare Act. The rehabilitation aims to avoid juvenile delinquency in the area and safeguard children by conducting various youth-oriented programs.The researchers used the descriptive method mixed with a phenomenological approach and a survey of the Bahay Kalinga about the problem encountered by barangay officials and security guards. Most respondents were 26-33 years old, male, married, and at the college level.The implementation of rehabilitation was interpreted as “very effective.” The study showed that the problem countered was “serious.” The researchers’ recommendation to improve and address the problem was interpreted as “very effective.”